Genomic data-sharing: what will be our legacy? - Callier, Shawneequa; Husain, Rajah; Simpson, Rachel (Frontiers in Genetics, 2014)
Prior to 1974, the Tuskegee Syphilis experiments, expansive use of the HeLa cells, and other blatant instances of research abuse pervaded the medical research field. Ongoing challenges to informed consent, privacy and data-sharing will influence the stories that research participants today share with future generations. This has significant implications for the advancement of genomic science, and the public's perception of genomic research.